2010
DOI: 10.1007/s12029-010-9190-8
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy for Colorectal Cancer Screening Above Age 75: Outcomes in Symptomatic African American and Hispanic Adults

Abstract: Symptomatic AAs and Hispanics ≥75 have a high incidence of CRC despite a previous normal colonoscopy. Presence of male sex, new onset anemia and hematochezia, and longer colonoscopy intervals are associated with CRC detection on colonoscopy. The detection of advanced cancer and high comorbidity/low life expectancy limit the benefit of CRC detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In older patients, procedure risk-benefit analysis needs to be individualized and considered based on each patient's comorbidities, symptoms, colonoscopy interval, and CRC risk factors. 29,30 This study has several limitations. Its retrospective nature means it is not possible to exclude all bias.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In older patients, procedure risk-benefit analysis needs to be individualized and considered based on each patient's comorbidities, symptoms, colonoscopy interval, and CRC risk factors. 29,30 This study has several limitations. Its retrospective nature means it is not possible to exclude all bias.…”
Section: Discussionmentioning
confidence: 96%
“…We did not, however, encounter any significant complications because of the colonoscopies, highlighting that the procedures are generally safe. In older patients, procedure risk–benefit analysis needs to be individualized and considered based on each patient's comorbidities, symptoms, colonoscopy interval, and CRC risk factors …”
Section: Discussionmentioning
confidence: 99%
“…Hispanics comprise the largest growing ethnicity in the US, and are estimated to reach a population of greater than 100 million individuals by 2050 . There is emerging evidence that colorectal neoplasia rates among Hispanics are similar to or possibly greater than those of whites, although studies to date have been limited to sigmoidoscopy, did not include whites as a comparison group, did not include histology or were limited to symptomatic individuals …”
Section: Introductionmentioning
confidence: 99%
“…3 There is emerging evidence that colorectal neoplasia rates among Hispanics are similar to or possibly greater than those of whites, although studies to date have been limited to sigmoidoscopy, 4 did not include whites as a comparison group, 5 did not include histology 6 or were limited to symptomatic individuals. 7 We aimed to compare the prevalence of histologically confirmed adenomas and advanced colorectal neoplasia among Hispanics and blacks as compared to whites among individuals undergoing screening colonoscopy at an urban medical centre that serves a racially and ethnically diverse patient population.…”
Section: Introductionmentioning
confidence: 99%
“…12 , 13 Singhal and colleagues found that although older adults, specifically African Americans and Hispanics, may have a previously normal colonoscopy, screening in ages 75 or older can still detect advanced CRC (19%). 14 About 5,200 middle-aged and older persons found a reduction of 65% in right-colon cancers and 75% in left-colon/rectal cancers after participating in CRC screening, specifically colonoscopy. 15 …”
Section: Introductionmentioning
confidence: 99%